2019
DOI: 10.19173/irrodl.v20i4.4385
|View full text |Cite
|
Sign up to set email alerts
|

Research on MOOCs in Major Referred Journals

Abstract: Over the last decade, several studies have focused on massive open online courses (MOOCs). The synthesis presented here concentrates on these studies and aims to examine the place held by content in these studies, especially those produced between 2012 and 2018: sixty-five peer reviewed papers are identified through five major educational technology research journals. The analysis revealed that these research articles covered a wide diversity of content. Content was mainly defined in terms of objectives of MOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…From these different perspectives, we have identified three common features of digital culture: its references characterized by the dominant digital uses and practices among young people and in our case prospective teachers, the products that result from these practices and uses, in terms of content, resources produced, etc., and the communication or exchanges through the digital tools used [17].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…From these different perspectives, we have identified three common features of digital culture: its references characterized by the dominant digital uses and practices among young people and in our case prospective teachers, the products that result from these practices and uses, in terms of content, resources produced, etc., and the communication or exchanges through the digital tools used [17].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Similarly, Snyder (2019) advocates on the use of literature review as a research methodology in business studies. Another scholar combined literature review approach and thematic content analysis to conduct research on role and place of content for massive open online courses (Babori et al, 2019). Therefore, this study uses integrative literature review methodology as well as content analysis to review studies in digital marketing and tourism relating to Africa with the main objective to explore digital marketing and tourism by focusing on opportunities for Africa, and specifically to examining social media marketing in relation to tourist arrivals.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings showed that most MOOC studies focused on addressing learners' completion, dropout rates, and retention. Babori et al (2019) examined the content of MOOC research in 65 peer-reviewed papers produced in five major educational technology research journals between 2012 and 2018. Their analysis revealed that these articles were mainly concerned with MOOCs' objectives, prerequisites required for participation in MOOCs, and types of learning scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some stakeholders have suggested that MOOCs may have a groundbreaking impact on higher education, potentially making traditional physical universities obsolete (Shirky, 2013). While acknowledging the potential of MOOCs, some educators have expressed concerns about the pedagogical models based on information transmission that have been widely applied in MOOCs (Albert et al, 2015;Babori et al, 2019;Veletsianos & Shepherdson, 2016;Zhu et al, 2018). Despite the polarized debate, the number of MOOC courses offered and students enrolled has continued to grow, which has aroused the interest of researchers.…”
Section: Introductionmentioning
confidence: 99%